A Comparative Analysis on Economic Roles of Government and Principles of Taxation between Public Economics and Siyasah Shar‘iyyah - Ariffin, Muhammad Irwan (Global Review of Islamic Economics and Business, 2023)
This research is an exploratory study on the similarities and differences of the justifications, objectives, roles of government and principles of taxation between public economics and siyasah shar‘iyyah. It aims to contribute towards integration of knowledge between modern economic theories and Islamic heritage in public economics. Despite similar focus on governance and social welfare, there is a lack of comparative study between public economics and siyasah shar‘iyyah in the literature. The research utilizes qualitative analysis on relevant textual materials on public economics and siyasah shar‘iyyah to identify and compare the major themes in terms of arguments for the establishment of a government, its economic objectives and roles, and taxation principles. The establishment of a government in public economics is based on the need to balance between efficiency and equity, address market failures, and provide public goods. Siyasah shari‘iyyah argues for a government based on fulfilling maqasid shari‘ah, uphold justice, and protect the rights of people. The principles of taxation in public economics often emphasize efficiency, equity, revenue sufficiency, neutrality, and administrative feasibility. In contrast, the principles of taxation in siyasah shar‘iyyah prioritize justice, prohibition of exploitation, funding public services, transparency and accountability, and wealth distribution in accordance with Islamic values. Originality/Value: The advancement of Islamic economics requires the integration of modern economic knowledge with divine revelation. Since public economics is a specialized subfield within economics, the integration efforts with siyasah shar‘iyyah have been notably deficient. This study aims to address this gap by undertaking a comparative analysis of fundamental principles and objectives between public economics and siyasah shar’iyyah.